Semiconductor Packaging Materials Interaction and Reliability - Chen, Andrea (Taylor & Francis, 2012)
In semiconductor manufacturing, understanding how various materials behave and interact is critical to making a reliable and robust semiconductor package. Semiconductor Packaging: Materials Interaction and Reliability provides a fundamental understanding of the underlying physical properties of the materials used in a semiconductor package. By tying together the disparate elements essential to a semiconductor package, the authors show how all the parts fit and work together to provide durable protection for the integrated circuit chip within as well as a means for the chip to communicate with the outside world. The text also covers packaging materials for MEMS, solar technology, and LEDs and explores future trends in semiconductor packages.